Analisis SWOT dalam Menetapkan Strategi Menjalankan BPJS Kesehatan pada Mitra Keluarga Kalideres - Martinus Limaku (Universitas Tarumanagara, 2019)
This study aims to analyze and determine the best strategy for Mitra Keluarga to be ready to join BPJS Kesehatan. Mitra Keluarga is a place that provides health services. This study used a SWOT analysis to get the best strategy for Family Partners. Data sources come from hospital managerial officers and from government regulations. The SWOT analysis is used to get the best strategy for Mitra Keluarga to find out what are the strengths, weaknesses, opportunities and threats of the company. Alternative strategies will be analyzed with everything that happens in the hospital or from outside the hospital. The conclusion of this study is to implement a strategy in running the Health BPJS on the Kalideres Family Partner in accordance with the company's external and internal conditions.